Glucose-albumin ratio (GAR) as a novel biomarker of postoperative urinary tract infection in elderly hip fracture patients - Wang, Wei; Tang, Wanyun; Yao, Wei; Lv, Qiaomei; Ding, Wenbo (Frontiers in Medicine, 2024)
Purpose: Postoperative urinary tract infections (UTIs) worsen the prognosis of elderly patients with hip fractures. This study aimed to assess the predictive ability of blood-based biomarkers, specifically the glucose-albumin ratio (GAR), in predicting postoperative UTIs.A retrospective observational study of 1231 patients from a Level I trauma center was conducted. We evaluated the prognostic and predictive value of 15 biomarkers, including the glucosealbumin ratio, in elderly patients with hip fractures. The primary outcome measure was the incidence of postoperative UTIs.The glucose to albumin ratio transformed into GAR was superior to any other biomarker in predicting postoperative UTIs in elderly hip fracture patients (AUC = 0.756, p < 0.001). Elevated GAR (using the best cut-off value of 0.18) was independently associated with postoperative UTIs (OR 3.20,. Further analysis dividing GAR levels into four groups according to quartiles showed that compared to patients with GAR levels of Q1 (< 0.14), GAR levels of Q2 (0.14-0.17; OR 2.11, 95%